2008
DOI: 10.1021/ja077921v
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Anisotropically Phase-Segregated Pd/γ-Fe2O3 Nanoparticles into Exchange-Coupled fct-FePd/α-Fe Nanocomposite Magnets

Abstract: Exchange-coupled fct-FePd/alpha-Fe nanocomposite magnets were fabricated by converting anisotropically phase-segregated Pd/gamma-Fe2O3 nanoparticles via the interfacial atom diffusion. The magnetically hard fct-FePd phases formed by the interdiffusion between alpha-Fe and fcc-Pd phases nearly preserve their sizes at the nanometer scale because they are surrounded by the alpha-Fe matrix. The VSM measurements reveal that the exchange coupling between the soft and hard phases has been realized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
51
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 16 publications
3
51
0
Order By: Relevance
“…8 and 9). These magnetic property values are comparable to those ( 0 H c = 0.076 T; J s = 1.31 T) of isotropic FePd/␣-Fe nanoparticles fabricated by chemical selfassembly after annealed at 500 • C for 3 h[17]. Recent results from the chemical self-assembly approach showed that annealing temperatures of 450-500 • C for a long annealing time up to 48 h provided better magnetic properties for the isotropic FePd/␣-Fe nanoparticles.…”
supporting
confidence: 72%
“…8 and 9). These magnetic property values are comparable to those ( 0 H c = 0.076 T; J s = 1.31 T) of isotropic FePd/␣-Fe nanoparticles fabricated by chemical selfassembly after annealed at 500 • C for 3 h[17]. Recent results from the chemical self-assembly approach showed that annealing temperatures of 450-500 • C for a long annealing time up to 48 h provided better magnetic properties for the isotropic FePd/␣-Fe nanoparticles.…”
supporting
confidence: 72%
“…Due to its low cost and the abundance of its raw materials in nature, Fe 2 O 3 has been widely investigated in many technological fields for applications such as energy materials for lithium ion storage, gas sensors, catalysts, and magnetic applications [1][2][3][4][5][6]. It is well known that the particle sizes and shapes of nanoscale materials affect their properties and potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…Iron oxide and oxyhydroxide iron have been extensively used in the production of pigments, catalysts, gas sensors, magnetic recordings, and raw materials for hard and soft magnets [1][2][3][4][5][6][7]. Among the iron oxides, ␣-Fe 2 O 3 has the corundum structure, while ␥-Fe 2 O 3 and Fe 3 O 4 have the spinel structure.…”
Section: Introductionmentioning
confidence: 99%